UJI ANTIOKSIDAN DENGAN METODE DPPH DARI FORMULASI LULUR KRIM EKSTRAK POLIFENOL Gelidium sp - Densi Selpia Sopianti (Jurnal Katalisator, 2020)
The use of scrubs with natural ingredients is increasingly widespread to prevent side effects from the use of chemicals, one of which is polyphenol compounds from Gelidium sp. The purpose of this study was to make scrubs from the extract of Gelidium sp polyphenol tested by antioxidants and the DPPH method. The method of making polyphenol extract with from Gelidium sp using 50% methanol and then made to scrub formulations with and multiplication of extraction of 10,15,20% and in physical properties testing including organoleptic test, pH tets, dispersion test, sticky power test, hedonic test, cream type test and antioxidant. The results of the study showed that the pysical properties of cream scrubs, in the organoleptic test, affected the shape and color. pH test, scattering power test, ticky strength affect the preparation because the more extracts are added into the preparation, the higher the value abtained. The most preferred formula by the researcher is in the formula 3 (three). Antioxidant test gets value IC50 vitamin C 435,79 ppm. While each formula gets a value formula 1 : 701,12 ppm, formula 2 : 679,32 ppm, dan formula 3 : 152,45 ppm.